Expression of MUC1, Thomsen-Friedenreich-related antigens, and cytokeratin 19 in human renal cell carcinomas and tubular clear cell lesions - Cao, Yi; Zerban, Heide; Bannasch, Peter (Virchows Archiv, 2000)
The expression of MUC1, MUC2, mucin-associated Thomsen-Friedenreich-related antigens (TF, sialosyl-TF, Tn, and sialosyl-Tn), and cytokeratin 19 (CK19) was systematically investigated in situ in 58 resected human kidney tumours, surrounding tissue of normal appearance, and two normal kidneys obtained at autopsy, using monoclonal antibodies.